The use of magnesium sulfate can reduce the mortality risk of cirrhosis patients: a retrospective cohort study - Chen, Boxian; Yang, Yuping; Liang, Mouji; Kou, Yanqi; Ye, Ruyin; Zhan, Liping; Huang, Yujie; Zhang, Qing; Huang, Haoyuan; Zheng, Jieming; Huang, Zhe; Ye, Shicai (Frontiers in Pharmacology, 2025)
BackgroundMagnesium deficiency is common in patients with cirrhosis, but there is a lack of real-world evidence to support the effect of magnesium supplementation on prognosis.ObjectiveTo explore whether magnesium sulfate supplementation is beneficial for patients with cirrhosis using data from the MIMIC-IV database.MethodsPatients with cirrhosis were divided into magnesium sulfate group and non-magnesium sulfate group according to medication use during hospitalization after admission to the intensive care unit (ICU). In-hospital all-cause mortality was the primary outcome, and 180-day all-cause mortality was the secondary outcome. Propensity score matching (PSM) method, univariate and multivariate regression analysis were used to evaluate the effect of magnesium sulfate on prognosis, and Kaplan-Meier curves, subgroup analysis and sensitivity analysis were performed to clarify the stability of the results.ResultsThe prematched cohort included 3,312 patients, while the propensity score matched cohort included 1,308 patients. In the PSM analysis, the in-hospital all-cause mortality in the magnesium sulfate group was 22.0% (144/654), and that in the non-use group was 31.0% (203/654). Magnesium sulfate use was associated with lower in-hospital mortality (odds ratio [OR], 0.47; 95% confidence interval [CI], 0.33–0.69; P < 0.001) and reduced all-cause mortality at 180 days after ICU admission (hazard ratio [HR], 0.61; 95% CI, 0.51–0.72; P < 0.001). Sensitivity analyses confirmed the robustness of these results.ConclusionMagnesium sulfate use is associated with reduced in-hospital and 180-day all-cause mortality in ICU patients with cirrhosis, which needs to be verified in prospective studies.